1991
DOI: 10.1128/iai.59.10.3619-3625.1991
|View full text |Cite
|
Sign up to set email alerts
|

Subclass distribution of salivary secretory immunoglobulin A antibodies to oral streptococci

Abstract: The ability of specific secretory immunoglobulin A (S-IgA) antibodies to inhibit bacterial colonization of mucosal surfaces may be neutralized by the activity of bacterial IgAl proteases. Because of the resistance of the IgA2 subclass to these enzymes, the biological effect of IgAl proteases in vivo may depend on the subclass distribution of the bacterium-specific antibodies. We have estimated the subclass distribution of S-IgA antibodies in saliva samples from 13 individuals against IgAl protease-producing (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Nunc polystyrene microplates (code, 269620) were used as solid phase throughout and proteins for coating were incubated at 5 μg/ml in 10 mM Tris buffered saline, pH 7.5 containing 0.1% sodium azide (TBS) in volumes of 100 μl at room temperature overnight. The TBS supplied with 0.15% Tween 20 (TBST) served as combined washing and blocking solution and as diluent for unknowns, standards, antibody reagents, and alkaline phosphatase conjugates, all of which were incubated at room temperature for 4 h. Pilot experiments showed that TBST used in this way, with the type of plates employed, prevented background reactions that may arise from nonspecific binding of test sample Igs and other postcoating reagents to the plate material (16). Optimal dilutions of commercial antibodies (from DAKO, Glostrup, Denmark, unless otherwise stated) were determined in pilot experiments.…”
Section: Quantitation Of Immunoglobulins and Albumin In Nasal Lavage mentioning
confidence: 99%
See 1 more Smart Citation
“…Nunc polystyrene microplates (code, 269620) were used as solid phase throughout and proteins for coating were incubated at 5 μg/ml in 10 mM Tris buffered saline, pH 7.5 containing 0.1% sodium azide (TBS) in volumes of 100 μl at room temperature overnight. The TBS supplied with 0.15% Tween 20 (TBST) served as combined washing and blocking solution and as diluent for unknowns, standards, antibody reagents, and alkaline phosphatase conjugates, all of which were incubated at room temperature for 4 h. Pilot experiments showed that TBST used in this way, with the type of plates employed, prevented background reactions that may arise from nonspecific binding of test sample Igs and other postcoating reagents to the plate material (16). Optimal dilutions of commercial antibodies (from DAKO, Glostrup, Denmark, unless otherwise stated) were determined in pilot experiments.…”
Section: Quantitation Of Immunoglobulins and Albumin In Nasal Lavage mentioning
confidence: 99%
“…Concerning the individual assay protocols, total IgA and IgG were quantitated by sandwich ELISA using isotype‐specific rabbit antibodies for coating and enzyme‐conjugated verions of the same antibodies for detection (third layer). Secretory‐IgA purified from human colostrum (16) served as standard in the IgA assay whereas isotype standards for the IgG assay were obtained from DAKO. Birch allergen‐reactive IgA and IgG antibodies in nasal wash were quantitated in gravimetric units (ng/ml) as described (17).…”
Section: Quantitation Of Immunoglobulins and Albumin In Nasal Lavage mentioning
confidence: 99%
“…ELISA assays were broadly based on sandwich assays previously developed [35][36][37][38][39]. However, these were substantially modified to increase sensitivity and thus detectability in GCF.…”
Section: Determination Of Igg and Iga Subclass Protein And Iga1 Fragmmentioning
confidence: 99%
“…Human dimeric IgAl (Kah) was isolated from the serum of a patient with multiple myeloma as previously described (5). The IgAl preparation was devoid of IgG and IgM and contained less than 5% IgA2, as tested by ELISA (2).…”
Section: Paraprotein Purificationmentioning
confidence: 99%
“…Fragments of IgAl (Fab, Fc, or Fc2.SC), indicating in vivo activity of IgAl proteases, have been demonstrated in intestinal fluid (25), in vaginal secretions of women with gonococcal infection (3), in cerebrospinal fluid from patients with H. influenzae meningitis (12), in nasopharyngeal secretions from children (19,38), in saliva and on the surface of dental plaque bacteria (1,2). Lack of evidence of in vivo activity of IgAl proteases from Prevotella and Capnocytophaga has been one of the reasons why their significance in the subgingival microenvironment so far has been speculative.…”
mentioning
confidence: 99%